Determination of anti-cancer effects of Nigella sativa seed oil on MCF7 breast and AGS gastric cancer cells - Çınar, İrfan; Gıdık, Betül; Dirican, Ebubekir (Springer Science and Business Media LLC, 2024)
This study aimed to investigate the cytotoxic, apoptotic, invasion, metastasis, and heat shock proteins (HSPs) effects of N. sativa oil on breast and gastric cancer cells.We assessed the cytotoxic and apoptotic effects of various concentrations of N. sativa oil (10-50-100-200 µg/mL) on MCF7 breast cancer and AGS, an adenocarcinoma of the gastric cell line, at 24, 48 and 72 h using the MTT test. Additionally, the expression of the Caspase-3, BCL2/Bax, MMP2-9 and HSP60-70 gene was examined using RT-PCR in cell lines treating with N. sativa.The MTT experiments demonstrate that N. sativa has a time and dose-dependent inhibitory effect on the proliferation of MCF7 and AGS cancer cells. The vitality rates of MCF7 and AGS cells treated with N. sativa were 77.04-67.50% at 24 h, 65.28-39.14% at 48 h, and 48.95-32.31% at 72 h. The doses of 100 and 200 µg/mL were shown to be the most effective on both cancer cells. RT-PCR analysis revealed that N. sativa oil extract increased caspase-3 levels in both cell lines at higher concentrations and suppressed BCL2/Bax levels. Exposure of MCF7 and AGS cell lines to N. sativa caused a significant decrease in the expression of MMP2-9 and HSP60-70 genes over time, particularly at a dosage of 200 µg/mL compared to the control group (p < 0.05).Our findings indicate that N. sativa oil has a dose-dependent effect on cytotoxicity and the expression of apoptotic, heat shock proteins, and matrix metalloproteinases genes in breast and gastric cancer.
Keywords: AGS; HSPs; Caspase 3; MCF7; Apoptosis; Antineoplastic Agents; N. sativa; Stomach Neoplasms; Cell Line, Tumor; MCF-7 Cells; Humans; Matrix Metalloproteinase 2; Plant Oils; MMPs; Nigella sativa; RT PCR; Heat-Shock Proteins; bcl-2-Associated X Protein; Cell Proliferation